Analysis of Outdoor Learning Model and Cognitive Learning Outcomes - Fitrianti, Fitrianti (Yayasan Meira Visi Persada, 2025)
This study aims to analyze the effect of an outdoor learning-based learning model on improving students' cognitive learning outcomes. The outdoor learning model is implemented through learning activities outside the classroom that link direct experience with the subject matter. The research method used was a quasi-experimental study with a pretest-posttest control group design. The research subjects consisted of high school students divided into two groups, namely the experimental and the control groups. Cognitive learning outcome data were collected through objective tests and analyzed using parametric statistical tests. The results revealed that there was a significant difference between the cognitive learning outcomes of students who participated in the outdoor learning model and those who used conventional learning. Therefore, the outdoor learning model can improve cognitive abilities and active student engagement in the learning process